Engaging Methods for Exploring 'Funds of Identity' in Early Childhood Contexts - Jacqueline D'warte; Christine Woodrow (MDPI AG, 2022)
Globalisation has contributed to increasing diversity with children and families, bringing multiple languages and cultures into early childhood settings around the world. While this has enhanced our settings, research suggests that educators are struggling to find ways to support children's learning and development in super diverse contexts. Standardised curriculum and pedagogy have complicated matters by suggesting that all children can achieve the same outcome if given the same program. Failing to recognize and acknowledge the complexity of teaching and learning in diverse settings leads to practices that position children and their families as deficient, viewing children and families based on what they lack rather than building from their strengths. In this manuscript we look through the theoretical lenses of funds of knowledge and funds of identity. The two constructs are brought together to explore how innovative, creative arts-based methods from two different research projects in ECE settings across Australia and Chile made children and families' funds of knowledge and funds of identity visible and potentially impacted learning, participants' perspectives, and community engagement in these diverse settings. We offer evidence of the ways arts-based methods promoted creativity and agency for all participants in and across both early learning contexts.